Synthesis and characterization of Mn doped ZnS pellets - Shukla, Atul; Srivastva, Anupam; Vishwakarma, Rahul (International Journal of Physical Research, 2014)
Semiconducting nano-phosphor pellets have been fabricated by hydraulic pressure, using ZnS and Mn doped ZnS semiconducting materials, which is synthesized by physical evaporation technique. Structural characterizations of synthesized semiconducting nanophosphor materials and pellets have been done by X-ray diffraction measurement and SEM while optical characterizations are done by UV-Visible absorption measurement. XRD pattern showed that the synthesized ZnS, Mn doped ZnS materials and pellet have cubic structure with preferential orientation along (111) planes. Optical absorption measurements indicated that the absorption decreases with increase of percent of Mn in pellet. The average maximum grain size (25.13 nm), Minimum dislocation density (1.57 × 1011/cm3), lattice constant (5.398Å) and minimum band gap (3.2 eV) have been obtained.  Suitable explanation is given in this paper. Keywords: ZNS, MN, Grain Size, Band Gap and Lattice Constant.